Application Of The Ahp Method In Decision Support System For Security Recruitment - Kurniawan, Agung; Fauzi, Achmad; Syahputra, Siswan (Yayasan Kita Menulis, 2023)
PT Perkebunan Nusantara II (PTPN II) Sei Semayang, a state-owned enterprise (BUMN) engaged in palm oil and sugarcane production. Security officers play a crucial role in maintaining the company's security and productivity. Currently, the security officer recruitment process remains conventional, relying on subjective assessments based on several criteria. The aim of this study is to introduce a more structured, transparent, and objective approach to security officer recruitment. By implementing the Analytic Hierarchy Process (AHP) method, decisions in selecting prospective security officers can be made based on predetermined criterion weights. AHP enables decision-makers to identify, compare, and prioritize relevant criteria, addressing the complexity of selecting candidates who fit the established criteria. Through this approach, the study seeks to enhance efficiency and effectiveness in the security officer selection process, reduce the risk of errors in candidate selection, and improve overall company performance and security. It is hoped that the application of the AHP method in the decision support system for security officer recruitment at PTPN II Sei Semayang will assist the company in optimizing the selection process and supporting more data-driven decision-making.